BUILDING BLOCKS OF LIFE IN METEORITES MAY LEAD TO PANSPERMIA ORIGIN OF LIFE - Rao, Y. V. Subba (International Journal of Research -GRANTHAALAYAH, 2021)
The current hypothesis leads to the panspermia origin of life, which is based on the scientific principle of electromagnetic force interaction with matter. Electromagnetic force (Sunlight) interacts with inorganic chemistry available to us given out by the stars in the universe plausibly triggers the formation of extra-terrestrial biological molecules of proto cells under abiotic conditions, as evidenced by their presence in meteorites.’ Proto cells’ might theoretically give rise to living organisms with a manifested soul, allowing ’Ribose’ to be formed from ice grains hit by sunlight for RNA and DNA at the same time. The presence of life’s building blocks and other important organic chemicals like ribose in meteorites, including some microscopic life forms that aren’t native to Earth, may have led to the ’Panspermia Origin of Life’ and the ’Evolution of Life on Earth’ which is evidenced by the definition of ’Meteorites’ in Vedic Scriptures, such as the "Bhagavad Gita" (3000 BC) and "Brihat Samhita" (520 AD) that they are the souls of righteous people who have returned to earth to be reborn.